Development budgeting: a case opening a new branch campus of ITM / Muhd Kamil Ibrahim - Ibrahim, Muhd Kamil (1988)
Development is a big yet persuasive word in nature, adopts by the ruling party during election campaigns ever since independence. The development which the goverment brought about seems to be a basis of performance evaluation and a deciding factor in ensuring the ruling party continued existence when the next election comes.